PENGHINDARAN WARIS MELAUI HIBAH DI PONDOK PESANTREN AL-HIKMAH BREBES - Sutrisno, Sutrisno (Mozaic : Islam Nusantara, 2021)
This study analyzes the pattern of inheritance distribution practices at the Al-Hikmah Islamic Boarding School in Brebes district. This paper uses the empirical research method with a qualitative approach, in this case, the researcher obtains data by interviewing, observing, and study document. This results in distribution of inheritance at the Al-Hikmah Islamic boarding school in Brebes district does not use Islamic law (faraidh science) but uses the practice of grants, this practice does not mean that Kyai and Islamic boarding schools as a source of scientific treasures turn away from Al-Hikmah. Qur'an and Sunnah, however, this method is a mursalah maslahah to avoid conflict among the kyai's family and Islamic boarding school. In this case, the implementation of the distribution of inheritance is based on what was agreed upon by the parties concerned and carried out for maslahah mursalah